Prognostic indicators for heart failure hospitalization in acute coronary syndrome patients: An observational study under the influenza vaccination trial - Apirak Sribhutorn (2018)
© 2018, Medical Association of Thailand. All rights reserved. Background: Heart failure [HF] is described as a consequence from tissue injury in myocardial infarction through finally organ failure. Therefore, HF prevention through forecasting clinical predictors is useful for closely HF monitoring and management. Objective: To explore prognostic indicators for HF hospitalization in Acute coronary syndrome [ACS] patients through the influenza vaccination trial. Materials and Methods: These observational data were collected from 439 ACS patients of Phrommintikul et al. The inactivated influenza vaccine was injected intramuscularly as a single dose in the vaccination group. The HF hospitalization outcome was determined through one-year follow-up time. The multivariable Cox’s regression model was performed to explore the prognostic values. Results: The significant prognostic indicators were female (HR 4.05, 95% CI 1.25 to 13.19, p = 0.020), dyslipidemia (HR 7.44, 95% CI 1.88 to 29.40, p = 0.004), elevated SCr (HR = 5.46, 95% CI 1.39 to 21.41, p = 0.015), impaired LVEF (HR 9.55, 95% CI 2.55 to 35.81, p = 0.001), and influenza vaccination (HR 0.25, 95% CI 0.07 to 0.86, p = 0.028). Conclusion: ACS patients who were female with dyslipidemia, elevated SCr, and impaired LVEF should be closely monitored for HF. The influenza vaccination had a significant protective effect for HF in ACS. Therefore, the benefit of influenza vaccine should be considered in practice for ACS patients.